Financial Inclusion as a Mechanism for Enhancing the Growth of Startups in Algeria - Madani, Wafaa; Guennoun, Amine (Journal of Ecohumanism, 2026)
This study aims to analyze the role of financial inclusion in supporting and developing startups in Algeria by highlighting its contribution to improving access to financing and financial services, as well as fostering innovation and entrepreneurship. The study is of particular importance due to its connection with one of the fundamental pillars of modern economic development, as startups represent an effective tool for wealth creation, job generation, and economic growth stimulation.The study adopted a descriptive-analytical approach by presenting the theoretical concepts related to financial inclusion and startups and analyzing statistical data concerning Algeria during the period 2022–2025 in order to explore the relationship between them.The findings revealed that the expansion of financial inclusion has facilitated startups’ access to financing and banking services, which has positively impacted their performance, sustainability, innovation capacity, and competitiveness. Furthermore, startups have contributed to job creation and the support of the national economy. In light of these findings, the study recommends strengthening financial literacy among entrepreneurs, expanding the use of digital financial services, supporting financial technology (FinTech), improving financial infrastructure, and simplifying financing procedures. These measures would contribute to enhancing financial inclusion and supporting the growth of startups in Algeria.